Biodegradable tissue repair functional dressing and preparation method thereof

The preparation of dressings that combine the functional membrane layer with high biocompatible and absorbing layer through electrospinning technology solves the problems of breathability and insufficient ooze absorption in chronic wound healing, and realizes cell migration and tissue growth, avoiding Secondary injury to the wound provides a stable healing environment.

CN119158061APending Publication Date: 2024-12-20修原(辽宁)生物有限公司

Patent Information

Application Number
CN202411666711.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing medical dressings lack the effect of promoting healing when treating chronic wounds, and frequent dressing replacement may lead to secondary damage to the wound. The repair film prepared by traditional spinning technology has failed to effectively solve the needs of high wound exudate absorption and breathability.

Method used

Electrospinning technology is used to prepare dressings that combine functional membrane layers with the absorption layer with biocompatible and extracellular matrix structure. By adjusting the spinning liquid formula, spinning parameters and absorption layer materials, high liquid absorption volume and breathability are achieved. and control the natural degradation of the membrane layer to avoid secondary damage to the wound.

Benefits of technology

The dressing promotes cell migration and proliferation, supports tissue growth and vascularization, maintains a wet healing environment for wounds, prevents exogenous contamination, and avoids wound damage during natural degradation, providing a stable and long-lasting healing environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158061A_ABST
    Figure CN119158061A_ABST
Patent Text Reader

Abstract

The invention relates to the field of medical dressings, in particular to a biodegradable tissue repair functional dressing and a preparation method thereof. The invention relates to a biodegradable tissue repair dressing, in particular to a chronic wound dressing (also known as a biodegradable tissue repair dressing) composed of a degradable electrostatic spinning functional film layer and an absorption layer (with or without a breathable film), and a preparation method and application of the biodegradable tissue repair dressing. The hydrogel can promote cell migration and proliferation, tissue growth and vascularization, has high wound seepage absorbability and air permeability, and provides a new method for treating acute and chronic wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a medical dressing, specifically a chronic wound dressing (also known as a biodegradable tissue repair functional dressing) composed of a degradable electrospinning functional membrane layer and an absorption layer (with or without a breathable membrane), and a preparation method and application thereof. The dressing not only has a structure similar to that of a natural extracellular matrix, and can promote cell migration and proliferation, tissue growth and vascularization, but also has high wound surface exudate absorption and breathability, providing a new method for treating acute and chronic wounds. Background Art

[0002] Medical dressings are medical materials that cover scalds, burns, ulcers or other damaged skin areas, and are intended to temporarily protect and heal damaged skin. These dressings have the functions of absorbing exudate, preventing exogenous contamination such as bacterial invasion, and promoting wound healing. Traditional medical dressings are usually made of gauze and cotton wool, which are relatively cheap and can protect damaged areas and reduce the risk of infection to a certain extent. However, these dressings are not suitable for infected wounds and do not promote wound healing. In addition, frequent changes of gauze may cause secondary damage to the wound skin, which is not conducive to wound healing.

[0003] Compared with traditional medical dressings, new medical dressings on the market can be divided into ointments, films, foams and gels. Film dressings have limited fluid absorption capacity; hydrocolloid dressings are usually used for moderately exudative wounds, but less for highly exudative wounds or neuropathic ulcers; hydrogel dressings are prone to cause problems such as accumulation of wound exudate and bacterial growth; polyurethane foam dressings have strong exudate absorption capacity and protection for wounds, but have not shown a positive effect in promoting wound healing.

[0004] Electrospun fibers are considered to be excellent tissue engineering materials due to their good biocompatibility, controllable mechanical properties and properties similar to natural extracellular matrix. Medical fiber membranes prepared based on electrospinning technology are one of the typical representatives of new medical dressings. They have characteristics such as high specific surface area, high porosity and excellent biocompatibility, which facilitate cell respiration and gas permeation, thereby preventing wound drying and dehydration. In terms of microstructure, electrospun fibers are similar to extracellular matrix networks, which can support the adhesion, proliferation, migration and differentiation of epithelial cells and endothelial cells, and play an important role in tissue regeneration and wound healing.

[0005] At present, in the domestic market, the products that have obtained registration certificates as repair membranes mainly include three categories: processed membrane products prepared with collagen as raw materials, such as: Fujian Bote Biological National Medical Device Registration No. 20173170525, Beijing Paisheng Biological National Medical Device Registration No. 20213171114, Tianxinfu (Beijing) Medical National Medical Device Registration No. 20223170809; decellularized extracellular matrix products prepared by post-processing, such as: Yantai Zhenghai Biological National Medical Device Registration No. 20153170386, National Medical Device Registration No. 20143132108, Shandong Junxiu Biological National Medical Device Registration No. 20193130355, Beijing Bohui Ruijin Biological National Medical Device Registration No. 20223170457; and freeze-dried film products prepared with raw materials such as polylactic acid, such as: Qingdao Jieshengbo Biological National Medical Device Registration No. 20233170232. However, the only repair membrane products made using electrospinning technology are Hubei Sairo Biotech's "Absorbable Silk Repair Membrane" (patent number CN103536958B, CN113293626A, national medical device registration number 20223171355) made using silk fibroin electrospinning, and Neumayr's three-layer composite membrane "Gelatin-Polycaprolactone Layered Gum Repair Membrane" (patent number CN109513046B, national medical device registration number 20223171355) made using gelatin and polycaprolactone electrospinning. Currently, no products made using electrospinning technology have been marketed as chronic wound dressings.

[0006] In the foreign market, products such as Apligraf, Integra, Dermafen, Dermagraft, Alloderm, and Lyphoderm have been approved by the U.S. Food and Drug Administration (FDA) and are widely used in the treatment of clinical skin defects. These products are mainly formed by implanting cells into a matrix (bovine collagen gel, polylactic acid network, and polyglycolic acid network). Therefore, using biodegradable polymer materials that have been commercialized and clinically used for nearly 30 years as raw materials, and through innovations in product form and process, the degradation time of the electrospinning functional membrane layer is close to or consistent with the wound healing cycle, thereby realizing the clinical application of biodegradable tissue repair functional dressings. Summary of the invention

[0007] In order to obtain an ideal medical dressing, the present invention provides a biodegradable tissue repair functional dressing and a preparation method thereof, which are designed to promote the regeneration of the dermis and epidermis of acute and chronic wounds. First, a spinning solution with a suitable concentration, component and ratio is selected, and the spinning parameters are adjusted to obtain an electrospinning functional membrane layer with a series of fiber diameter sizes, pore sizes, porosity and thickness; at the same time, the appropriate spinning solution formula, electric field strength, spinning speed and other spinning conditions also ensure the bonding strength between the electrospinning functional membrane layer and the absorption layer, which can satisfy the requirement of leaving the electrospinning functional membrane layer in place (wound surface) when replacing the biodegradable tissue repair functional dressing. In addition, the absorption layer gives the biodegradable tissue repair functional dressing high liquid absorption, air permeability and comfort. In general, the biodegradable tissue repair functional dressing greatly promotes cell migration and proliferation through a biomimetic structure (fiber structure) similar to the human extracellular matrix, and the excellent pore structure also promotes tissue growth and vascularization. The reasonable natural degradation cycle also ensures that there is no secondary wound damage caused by tearing or cleaning.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A biodegradable tissue repair functional dressing, comprising an electrospinning functional membrane layer and an absorption layer, wherein the electrospinning functional membrane layer is prepared from a biodegradable high molecular polymer by an electrospinning technology, and the biodegradable high molecular polymer is selected from one or more of polydioxanone (PPDO), polyε-caprolactone (PCL), polydioxanone-ε-caprolactone copolymer (PDCL), polyglycolic acid (PGA), polyvinyl lactone-ε-caprolactone copolymer (PGCL), polylactic acid-glycolic acid copolymer (PLGA), polydextrorotatory lactic acid (PDLA), polylactic acid-ε-caprolactone copolymer (PLCL), polylactic acid (PLLA), polytrimethylene carbonate (PTMC), polydodecylglycerol (PGD), and poly(ω-pentadecanolactone) (PPDL); one side of the absorption layer is provided with or without a breathable membrane.

[0009] The fiber diameter of the electrospun functional membrane layer is 1 nm to 2000 nm (preferably 100 nm to 1500 nm, more preferably 350 nm to 1500 nm).

[0010] The porosity of the electrospinning functional membrane layer is greater than 40% (preferably greater than 50%, more preferably greater than 60%), and the average pore size is 1 μm to 1000 μm (preferably 1 μm to 800 μm, more preferably 3 μm to 500 μm).

[0011] The thickness of the electrospinning functional membrane layer is 0.1 μm to 1000 μm (preferably 10 μm to 500 μm, more preferably 50 μm to 300 μm).

[0012] The material used for the absorption layer is any one or more of fibers, gels, hydrocolloids, foaming materials, etc. (preferably cotton fibers, hydrophilic fiber dressings, synthetic fiber gauze, paste gels or sheet gels composed of non-sticky multi-molecular polymers, sodium carboxymethyl cellulose hydrocolloids, synthetic elastomers, surface polyurethane semipermeable membranes, polyurethane foaming materials, and polyvinyl alcohol foaming materials; more preferably cotton fibers, synthetic fiber gauze, paste gels or sheet gels composed of non-sticky multi-molecular polymers, and polyurethane foaming materials). When one side of the absorption layer is provided with a breathable film, the breathable film is selected from any one of polyethylene (PE) film, polypropylene (PP) film, polyurethane (PU) film, etc. The thickness of the absorption layer is 0.1 mm to 5 mm, wherein the thickness of the breathable film is 0.012 mm~0.035 mm.

[0013] When one side of the absorption layer is provided with a breathable film, the electrospinning functional film layer is located on the side of the absorption layer without the breathable film, and the bonding strength between the electrospinning functional film layer and the absorption layer is 1-5 N / cm.

[0014] The preparation method is as follows: first, one or more biodegradable polymer materials are used as raw materials and volatile organic reagents are used as solvents, and the two are dissolved in a certain concentration, component and ratio to prepare a spinning solution. Then, an absorption layer with or without a breathable membrane is used as a receiving substrate, and the spinning parameters are reasonably adjusted to obtain a biodegradable tissue repair functional dressing. Compared with the prior art, the electrospinning functional membrane layer of the functional dressing has fiber diameters, pore sizes, and porosities of different scales; and the bonding strength with the absorption layer can ensure that the electrospinning functional membrane layer is left in place when the absorption layer is replaced, so that the progress of cell migration and proliferation, tissue growth and vascularization is not destroyed. At the same time, the electrospinning functional membrane layer can be naturally degraded without tearing or cleaning, avoiding secondary damage to the wound during the debridement process. In addition, the absorption layer with a breathable membrane also has the ability to absorb high liquid, breathability, comfort, waterproof and prevent exogenous pollution such as bacterial invasion.

[0015] Another object of the present invention is to provide a method for preparing a biodegradable tissue repair functional dressing, which can be achieved by the following technical scheme: comprising the following steps: (1) Preparing a spinning solution: adding a biodegradable high molecular polymer to a volatile organic reagent, stirring at a certain temperature until the polymer is completely dissolved, and preparing the desired spinning solution; (2) Under environmental conditions of a temperature of 18-40°C and a humidity of 30%-80% (preferably 18-30°C, 30%-60%, more preferably 20-30°C, 40%-60%), the spinning solution is loaded into a syringe with a metal needle, and the syringe and the injection pump are connected to each other; (3) connecting the metal needle in step (2) to the positive electrode, connecting the receiving end to the negative electrode, and fixing a receiving substrate with an area of ​​30 cm×20 cm (preferably 30 cm×10 cm, more preferably 10 cm×10 cm) on the outer surface of the receiving end; (4) After fixing the distance between the two electrodes, adjust the scanning length, cleaning length, scanning speed, cleaning speed, cleaning cycle, acceleration time, spinning time, cleaning time, micro pump flow rate, and receiving speed of the electrospinning machine in turn, and then apply high voltage. After the spinning is completed, the electrospun fiber membrane and the receiving substrate are retained at the same time, and the electrospun fiber membrane and the receiving substrate are not separated, and the prepared biodegradable tissue repair functional dressing is obtained.

[0016] Furthermore, the biodegradable high molecular polymer in step (1) may be one or more of polydioxanone (PPDO), polyε-caprolactone (PCL), polydioxanone-ε-caprolactone copolymer (PDCL), polyglycolic acid (PGA), polyvinyl lactone-ε-caprolactone copolymer (PGCL), polylactic acid-glycolic acid copolymer (PLGA), polydextrorotatory lactic acid (PDLA), polylactic acid-ε-caprolactone copolymer (PLCL), polylactic acid (PLLA), polytrimethylene carbonate (PTMC), polydodecylglycerol (PGD), and poly(ω-pentadecanolactone) (PPDL).

[0017] Furthermore, the mass percentage of the biodegradable high molecular polymer in the spinning solution in step (1) is 1-40 wt% (preferably 1-30 wt%, more preferably 5-20 wt%); Preferably, the volatile organic reagent in step (1) may be one or more of chloroform, methanol (MT), toluene (TL), dichloromethane (DCM), hexafluoroisopropanol (HFIP), tetrahydrofuran (THF), acetone (CP), N,N'-dimethylformamide (DMF); Preferably, the stirring rate in step (1) is 50-1500 rpm and the time is 2-48 h; More preferably, the stirring temperature in step (1) is 30-80 °C.

[0018] The type of the metal needle in step (2) is 10 G ~ 30 G (preferably 15 G ~ 30 G, more preferably 20 G ~ 30G); The volume of the syringe in step (2) is 1 mL to 50 mL (preferably 5 mL to 30 mL, more preferably 5 mL to 20 mL).

[0019] In step (3), the receiving end may be a metal plate, a roller or a metal wire; In step (3), the receiving substrate is an absorbent layer with or without a breathable membrane, and the absorbent layer material is any one or more of fiber, gel, hydrocolloid, and foaming material (preferably cotton fiber, hydrophilic fiber dressing, synthetic fiber gauze, paste gel or sheet gel composed of non-sticky multi-molecular polymer, sodium carboxymethyl cellulose hydrocolloid, synthetic elastomer, surface polyurethane semipermeable membrane, polyurethane foaming material and polyvinyl alcohol foaming material; more preferably cotton fiber, synthetic fiber gauze, paste gel or sheet gel composed of non-sticky multi-molecular polymer, polyurethane foaming material), wherein the breathable membrane is polyethylene (PE) film, polypropylene (PP) film, polyurethane (PU) film, and more preferably polyurethane (PU) film; The distance between the two poles in step (4) is 5 to 30 cm (preferably 5 to 20 cm, more preferably 8 to 15 cm); The scanning length in step (4) is 5 to 50 cm (preferably 5 to 40 cm, more preferably 10 to 30 cm); The cleaning length in step (4) is 5 to 20 cm (preferably 5 to 15 cm, more preferably 5 to 10 cm); The scanning speed in step (4) is 5 to 300 mm / s (preferably 10 to 150 mm / s, more preferably 20 to 100 mm / s); The cleaning speed in step (4) is 5 to 300 mm / s (preferably 10 to 150 mm / s, more preferably 20 to 100 mm / s); The cleaning cycle in step (4) is 1 to 30 times (preferably 1 to 15 times, more preferably 3 to 10 times); The acceleration time in step (4) is 1 to 600 s (preferably 1 to 300 s, more preferably 10 to 150 s); The spinning time in step (4) is 1 to 24 h (preferably 2 to 12 h, more preferably 4 to 8 h); The cleaning time in step (4) is 1 to 24 h (preferably 2 to 12 h, more preferably 4 to 8 h); The flow rate of the micro pump in step (4) is 0.1-20 mL / h (preferably 0.1-10 mL / h, more preferably 0.5-5 mL / h); The receiving rotation speed in step (4) is 1 to 5000 rpm (preferably 10 to 3000 rpm, more preferably 50 to 1500 rpm); The high voltage applied in step (4) is 1-30 KV (preferably 5-25 KV, more preferably 10-22 KV).

[0020] The present invention promotes cell migration and proliferation, tissue growth and vascularization by means of the biomimetic structure (fiber structure) and pore structure similar to the human extracellular matrix in the biodegradable tissue repair functional dressing; at the same time, it absorbs tissue exudate, maintains a moist healing environment for the wound, prevents exogenous pollution such as water and bacteria invasion, and avoids secondary damage caused by tearing or cleaning. The biodegradable tissue repair functional dressing is simply divided into an electrospinning functional membrane layer and an absorption layer (with or without a breathable membrane). For example, a polyurethane foam material with a PU membrane is selected as the absorption layer. The schematic diagram of its structure is shown in Figure 1 .

[0021] First, an electrospun functional membrane layer that can mimic the size and structure of natural extracellular matrix fibers, with fiber diameters ranging from about 30 nm to 2000 nm, pore sizes ranging from 3 μm to 500 μm, and porosity > 60%. In natural skin, the extracellular matrix is ​​composed of non-woven collagen fibers with diameters of about 50 to 500 nm; and electrospun fibers can support cell ingrowth and migration, which is of great benefit to successful wound healing. Synthetic fibers with diameters of 350 nm to 1100 nm can affect the diffusion, migration, and phenotype of adherent fibroblasts and mesenchymal stem cells (MSCs), so the electrospun functional membrane layer can promote cell proliferation and migration and achieve regeneration. At the same time, pore sizes of 5 μm to 15 μm are sufficient to support fibroblast ingrowth, 20 μm to 125 μm can promote skin regeneration, and pore sizes of 5 µm to 500 µm can help the formation of new blood vessels, reducing cell death and tissue necrosis caused by the loss of new blood vessels. The highly porous matrix (porosity 60%~90%) is conducive to cell infiltration and tissue growth; therefore, the electrospun functional membrane layer is sufficient to support cell ingrowth and the formation of new blood vessels, as well as the transportation of oxygen, nutrients and waste. In addition, the use of biodegradable polymer raw materials can resist the rapid degradation of enzymes at the wound site and avoid chronic wound non-healing caused by premature degradation of proteases. In addition, as the electrospun functional membrane layer is gradually absorbed in the body, the porosity will gradually increase, further promoting cell proliferation, migration and differentiation as well as rapid tissue growth.

[0022] Secondly, the polyurethane foam material with PU film can not only absorb excess tissue exudate and replenish the missing moisture in the wound to maintain a moist healing environment, but also balance the pressure on the wound surface to provide appropriate pressure. The PU film has a certain softness and breathability on the basis of waterproofing and preventing exogenous pollution such as bacterial invasion, which makes the polyurethane foam material with PU film provide a comfortable experience while maintaining its basic functions.

[0023] Finally, in the process of replacing the biodegradable tissue repair functional dressing, the bonding strength between the electrospun functional membrane and the polyurethane foam material can keep the functional membrane on the wound surface, providing a more stable and durable tissue scaffold for supporting wound healing for a long time, ensuring that cell migration and proliferation, tissue growth and vascularization are not affected, and avoiding secondary damage caused by frequent dressing changes and wound debridement.

[0024] Compared with the prior art, the technical problems to be solved by the present invention are mainly to innovate the formulation of biodegradable spinning solution, provide a preparation process of biodegradable tissue repair functional dressing, select the absorption layer material, and adjust the bonding strength between the electrospinning functional membrane layer and the absorption layer, so as to obtain a biodegradable tissue repair functional dressing that can promote cell migration and proliferation, tissue growth and vascularization, absorb tissue exudate, maintain a moist healing environment for the wound surface, prevent water and exogenous pollution, and avoid secondary damage caused by tearing or cleaning. The beneficial effects obtained by the present invention are as follows: The present invention innovates the biodegradable spinning solution formula, uses biodegradable high molecular polymer as raw material, and controls its degradation cycle to about 7 days to 24 months, so as to reduce the risk of chronic wound non-healing caused by enzymatic degradation at the wound site.

[0025] The present invention provides a preparation process of a biodegradable tissue repair functional dressing. By adjusting spinning parameters such as applied voltage, micropump flow rate, scanning speed and receiving rotation speed, the biodegradable tissue repair functional dressing is endowed with the ability to promote cell migration and proliferation, tissue growth and vascularization of the wound surface, and to absorb tissue exudate, maintain a moist healing environment of the affected area, and prevent exogenous pollution such as water and bacterial invasion.

[0026] The present invention selects the absorption layer and clarifies that the polyurethane foam material with a PU film has a strong liquid absorption capacity and a protective property for wounds.

[0027] The present invention obtains a suitable spinning solution formula, electric field strength, and spinning speed by regulating the concentration, components and ratio of the biodegradable spinning solution, the applied voltage, the flow rate of the micropump, and the scanning speed, thereby indirectly controlling the bonding strength between the electrospinning functional membrane and the polyurethane foam material in the biodegradable tissue repair functional dressing, thereby avoiding secondary damage caused by frequent dressing changes and wound debridement.

[0028] The present invention provides a biodegradable spinning solution formula, and obtains a biodegradable tissue repair functional dressing by using an electrostatic spinning process. The dressing is prepared by using a biodegradable high molecular polymer as a raw material to prepare a spinning solution, and through continuous adjustment and optimization of spinning parameters, an electrostatic spinning functional membrane layer of the size and structure of an extracellular matrix fiber is obtained, wherein the fiber diameter ranges from 30 nm to 2000 nm, the pore size ranges from 3 μm to 600 μm, the porosity is greater than 60%, and the degradation cycle is controlled to be about 7 days to 24 months. The film can not only promote cell proliferation and migration, the formation of new blood vessels, and the transportation of oxygen, nutrients and waste, but also further promote the rapid growth of tissues and resist the chronic wound non-healing caused by premature degradation of enzymes at the wound surface as the electrostatic spinning functional membrane layer gradually degrades on the wound surface. Secondly, the polyurethane foam material with a PU film can not only absorb excess tissue exudate, maintain a moist healing environment for the wound, and protect the wound surface from contamination, but also has air permeability and comfort. Finally, the appropriate bonding strength between the electrospun functional membrane and the polyurethane foam material allows the electrospun functional membrane to remain on the wound surface, ensuring that even if the biodegradable tissue repair functional dressing is frequently replaced, a more stable and lasting wound healing environment can be created, opening up a new way to improve the regeneration of the dermis and epidermis of chronic wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of the structure of the biodegradable tissue repair functional dressing provided by the present invention; wherein: 1. PU film; 2. polyurethane foam material; 3. electrospinning functional film; Figure 2 This is a SEM image of the electrospinning functional membrane provided by the present invention; Figure 3 The infrared spectrum of the electrospinning functional membrane provided by the present invention; Figure 4 The in vitro cytotoxicity comparison diagram of the biodegradable tissue repair functional dressing provided by the present invention, wherein (a) is the proliferation number and density of cells under a biological microscope of the negative control group, and (b) is the proliferation number and density of cells under a biological microscope of the experimental group. DETAILED DESCRIPTION

[0030] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0031] Any features such as preparation methods, materials, structures or composition ratios that are not clearly described in this technical solution shall be deemed as common technical features disclosed in the prior art.

[0032] In the present invention, the raw materials, consumables and equipment used in the preparation are as follows: Raw materials and consumables: polylactic acid-co-glycolic acid (PLGA) and polydioxanone (PPDO) were purchased from Suzhou Qihang Biotechnology Co., Ltd.; high-density polyethylene membrane, hexafluoroisopropanol (HFIP), and phosphate buffer solution (PBS) were purchased from Shanghai Roen Chemical Technology Co., Ltd.; polyurethane foam materials with or without PU membrane were purchased from Suzhou Yousichuang Materials Technology Co., Ltd.; MEM culture medium (containing 100 IU / mL penicillin and 100 μg / mL streptomycin) was purchased from Bio-Channel, mouse fibroblasts (L-929 cells), and fetal bovine serum were purchased from Adamas life sciences. ® PBS was purchased from Biosharp; reagent bottles and dishes were purchased from Nantong Hairui Experimental Equipment Co., Ltd.; latex gloves were purchased from Jiangsu Yangzi Lide Medical Equipment Co., Ltd.

[0033] Equipment: TL-BM-300 high-voltage electrospinning machine (equipped with syringe and metal needle) was purchased from Tongli Micro-Nano Technology Co., Ltd.; Hitachi Regulus8100 scanning electron microscope (SEM) was purchased from HITACHI, Japan; Autopore V 9620 high-performance fully automatic mercury intrusion instrument was purchased from Micromeritics (Shanghai) Instrument Co., Ltd.; 400MHz liquid nuclear magnetic resonance spectroscopy (NMR) was purchased from Bruker (Beijing) Technology Co., Ltd.; Fisher Scientific Nicolet iS20 Fourier transform infrared spectrometer (FTIR) and FORMASTERI-CYCLEi160LK CO2 incubator were purchased from Thermo Fisher Scientific; WDW-0.5 electronic universal testing machine was purchased from Shanghai Hualong Testing Instrument Co., Ltd.; CKX53 inverted biological microscope was purchased from Olympus Corporation.

[0034] Example 1

[0035] This example provides a biodegradable tissue repair functional dressing prepared by using an electrospinning functional membrane layer and an absorption layer formed by a single high molecular polymer component, wherein the absorption layer is a polyurethane foam material, and comprises the following steps: (1) 10 g of poly(lactic acid-co-glycolic acid) (PLGA) and 90 g of hexafluoroisopropanol (HFIP) were added into a reagent bottle equipped with a magnetic stirring bar. The mixture was stirred at 500 rpm for 8 h in an oil bath at 50 °C until the mixture was completely dissolved. A biodegradable spinning solution containing 10 wt% PLGA was obtained.

[0036] (2) Under the environmental conditions of temperature of 25 °C and humidity of 50%, take 20 mL of biodegradable spinning solution containing 10 wt% PLGA and load it into a 20 mL syringe with a metal needle (model 20 G), and ensure that the syringe and the injection pump are connected to each other.

[0037] (3) The metal needle in step (2) is connected to the positive electrode, the receiving roller is connected to the negative electrode, and a polyurethane foam material (absorption layer) with an area of ​​30 cm × 20 cm is adhered to the outer surface of the receiving roller.

[0038] (4) After fixing the distance between the two electrodes at 15 cm, the scanning length of the TL-BM-300 high-voltage electrospinning machine was adjusted to 25 cm, the cleaning length was 10 cm, the scanning speed was 100 mm / s, the cleaning speed was 100 mm / s, the cleaning cycle was 10 times, the acceleration time was 60 s, the spinning time was 2 h, the cleaning time was 2 h, the micro pump flow rate was 10 mL / h, and the receiving roller speed was 600 rpm. Then, a high voltage of 15 KV was applied. After the spinning was completed, the electrospun fiber membrane and the polyurethane foam material were retained at the same time, and the electrospun fiber membrane and the polyurethane foam material were not separated, and finally a biodegradable tissue repair functional dressing 1 was obtained.

[0039] The electrospun functional film layer of the biodegradable tissue repair functional dressing 1 was characterized, and the results were as follows: Regulus8100 scanning electron microscope (SEM) showed that its fiber diameter was about 300 nm~800 nm and the film thickness was about 50 μm. Figure 2 As shown in (a), the fiber diameter is uniform and has a small coverage area; the fiber pore size is in the range of 1 μm~600 μm and the porosity is >85% as measured by Autopore V 9620 high-performance fully automatic mercury intrusion instrument; 400MHz liquid nuclear magnetic resonance spectroscopy (NMR) and Fisher Scientific Nicolet iS20 Fourier transform infrared spectroscopy (FTIR) verify that the composition contains polylactic acid-co-glycolic acid (PLGA), such as Figure 3 (a) shows that the wave number is 2955.62 cm -1 The peak at 3000 cm is attributed to the methyl groups in PLGA (CH3, 3000 cm -1 ~2800cm -1 ) and methylene groups (CH2, 3000cm -1 ~2800cm -1 ) stretching vibration; the wave number is 1422.23 cm -1 The peak at 1450 cm is attributed to the methyl groups in PLGA (CH3, 1450 cm -1 ~1350cm -1 ) bending vibration; the wave number is 1748.32 cm -1 The peak at 1750 cm is attributed to the ester bond (C=O, 1750 cm -1 ~1350cm -1 ) stretching vibration; the wave number is 1147.27 cm -1 and 1272.85 cm -1 The peak at 1280 cm is attributed to the ester bond (COC, 1280 cm -1 ~1100cm -1 ) stretching vibration; the wave number is 1397.27cm -1 The peak at 1400 cm is attributed to the primary and tertiary alcohols in PLGA. -1 ). In summary, the infrared spectrum has the characteristic peaks of PLGA, that is, the component composition is PLGA. A phosphate buffer solution (PBS, PH=7.44) at 37 °C was selected as the in vitro degradation environment of the PLGA electrospinning functional membrane in the biodegradable tissue repair functional dressing 1. The obtained biodegradable tissue repair functional dressing 1 was immersed in a phosphate buffer solution at 37 °C, and the degradation time of the electrospinning functional membrane was about 16 days.

[0040] Next, the performance of the polyurethane foam material (absorption layer) was characterized according to the standard test methods specified in YY T 0471.1-2004, YYT 0471.2-2004, and YYT 0471.3-2004, and the following conclusions were drawn: the liquid absorbency was not less than 9 times the initial mass (the sum of the masses of the electrospun functional membrane and the polyurethane foam material with an area of ​​10 cm × 10 cm); the liquid absorption was not less than 10.0 g·24 h -1 ; Water vapor transmission rate not less than 800 g·m -2 24h -1; The water barrier property reached the standard of being able to withstand 500 mm hydrostatic pressure for 300 s without water seepage. Finally, the bonding strength between the electrospun functional membrane and the polyurethane foam material was tested using a WDW-0.5 electronic universal testing machine, and the average force required for each 1 cm width was not less than 0.6 N, which allowed the polyurethane foam material that had absorbed tissue exudate to be peeled off as needed during wound healing.

[0041] Example 2

[0042] The process and conditions are the same as in Example 1, except that: This embodiment provides a polyurethane foam material with a PU film on one side as an absorption layer, replacing the polyurethane foam material in the above embodiment 1 to obtain a biodegradable tissue repair functional dressing 2. The difference is that compared with embodiment 1, there is an additional layer of breathable film (PU film, thickness of 0.035 mm). In addition to exerting the essential function of the PU film, the performance of the polyurethane foam material in the biodegradable tissue repair functional dressing 2 is also slightly changed. The specific experimental content is as follows: Under the environmental conditions of 25 °C and 50% humidity, 20 mL of the biodegradable spinning solution 1 containing 10 wt% PLGA was taken and loaded into a 20 mL syringe with a metal needle (model 20 G), and the syringe was ensured to be connected to the injection pump.

[0043] The metal needle in step (1) was connected to the positive electrode, the receiving roller was connected to the negative electrode, and a polyurethane foam material (absorption layer) with a PU film on one side having an area of ​​30 cm×20 cm was adhered to the outer surface of the receiving roller.

[0044] After fixing the distance between the two electrodes at 15 cm, the scanning length of the TL-BM-300 high-voltage electrospinning machine was adjusted to 25 cm, the cleaning length was 10 cm, the scanning speed was 100 mm / s, the cleaning speed was 100 mm / s, the cleaning cycle was 10 times, the acceleration time was 60 s, the spinning time was 2 h, the cleaning time was 2 h, the micro pump flow rate was 10 mL / h, and the receiving roller speed was 600 rpm. Then, a high voltage of 15 KV was applied. After the spinning was completed, the electrospun fiber membrane and the polyurethane foam material with PU membrane were retained at the same time, and the electrospun fiber membrane and the polyurethane foam material with PU membrane were not separated, and finally a biodegradable tissue repair functional dressing 2 was obtained.

[0045] Since the components, concentrations and ratios of the electrospinning functional membrane layers of the biodegradable tissue repair functional dressing 1 and the biodegradable tissue repair functional dressing 2 are the same, and the spinning parameters are also the same, they will not be described again here.

[0046] Similarly, the polyurethane foam material with PU film (absorption layer with breathable film) was characterized according to the standard test methods specified in YY T 0471.1-2004, YYT 0471.2-2004, and YYT 0471.3-2004. It was found that the addition of PU film did not affect the main performance parameters of polyurethane foam material. The specific results are as follows: the liquid absorbency is not less than 9 times the initial mass (the sum of the mass of the electrospinning functional membrane and the polyurethane foam material with an area of ​​10 cm×10 cm); the liquid absorption is not less than 10.0 g·24 h -1 ; Water vapor transmission rate not less than 400 g·m -2 24h -1 Compared with the biodegradable tissue repair functional dressing 1, the value is lower, indicating that the PU film prevents excessive evaporation of water and maintains a certain air permeability on the basis of maintaining waterproof and anti-bacterial invasion and other exogenous pollution, and always maintains a moist healing environment for the wound surface; the water barrier reaches the standard of being able to withstand 500 mm hydrostatic pressure for 300 s without water seepage. Finally, the WDW-0.5 electronic universal testing machine was used to test the bonding strength between the electrospun functional membrane and the polyurethane foam material, and the average force required for each 1 cm width was not less than 0.6 N, so that it can meet the requirements of peeling off the polyurethane foam material that has absorbed tissue exudate as needed during the wound healing process.

[0047] Example 3

[0048] This example provides a biodegradable tissue repair functional dressing prepared by using an electrospinning functional membrane layer and an absorption layer formed by two different polymers. The basic structural parameters of the electrospinning functional membrane layer and the bonding strength between the electrospinning functional membrane and the polyurethane foam material can be compared with those in Example 1. The preparation includes the following steps: 10 g of poly(lactic acid-co-glycolic acid) (PLGA) and 40 g of hexafluoroisopropanol (HFIP) were added to a reagent bottle equipped with a magnetic stirring bar and stirred at a stirring rate of 500 rpm for 8 h in an oil bath at 50 °C until completely dissolved to obtain a biodegradable spinning solution containing 20 wt% PLGA.

[0049] 10 g of polydioxanone (PPDO) and 40 g of hexafluoroisopropanol (HFIP) were added to a reagent bottle equipped with a magnetic stirring bar, and stirred at a stirring rate of 500 rpm for 8 h in an oil bath at 50 °C until completely dissolved to obtain a biodegradable spinning solution containing 20 wt% PPDO.

[0050] Then, 10 mL of biodegradable spinning solution containing 20 wt% PLGA and 10 mL of biodegradable spinning solution containing 20 wt% PPDO were taken respectively and added into a reagent bottle equipped with a magnetic stirring bar. The mixture was stirred continuously at a stirring rate of 500 rpm for 2 h in an oil bath at 50 °C until the mixture was uniformly mixed, thereby obtaining a biodegradable spinning solution with a total content of PLGA and PPDO of 20 wt%.

[0051] Under the environmental conditions of temperature of 25 ℃ and humidity of 50%, 20 mL of biodegradable spinning solution with a total content of PLGA and PPDO of 20 wt% was taken into a 20 mL syringe with a metal needle (model 20 G), and the syringe was connected to the injection pump.

[0052] The metal needle in step (1) was connected to the positive electrode, the receiving roller was connected to the negative electrode, and a polyurethane foam material (absorption layer) with an area of ​​30 cm × 20 cm was adhered to the outer surface of the receiving roller.

[0053] After fixing the distance between the two electrodes at 15 cm, the scanning length of the TL-BM-300 high-voltage electrospinning machine was adjusted to 25 cm, the cleaning length was 10 cm, the scanning speed was 100 mm / s, the cleaning speed was 100 mm / s, the cleaning cycle was 10 times, the acceleration time was 60 s, the spinning time was 4 h, the cleaning time was 4 h, the micro pump flow rate was 5 mL / h, and the receiving roller speed was 300 rpm. Then, a high voltage of 22 KV was applied. After the spinning was completed, the electrospun fiber membrane and the polyurethane foam material were retained at the same time, and the electrospun fiber membrane and the polyurethane foam material were not separated, and finally a biodegradable tissue repair functional dressing 3 was obtained.

[0054] The electrospun functional membrane layer of the biodegradable tissue repair functional dressing 3 was characterized and analyzed, and the results were as follows: Regulus8100 scanning electron microscope (SEM) showed that its fiber diameter was about 30 nm~1500 nm and the film thickness was about 100 μm. Figure 2As shown in (b), the fiber diameter size is more serialized (the fiber diameter size covers a wider range and changes in a gradient), which is more in line with the needs of different cells for proliferation, migration and differentiation; the fiber pore size is measured by Autopore V 9620 high-performance fully automatic mercury intrusion instrument in the range of 3 μm~500 μm, and the porosity is greater than 60%. Although the pore size and porosity values ​​have decreased, this is mainly attributed to the increase in fiber diameter, and it still supports the ingrowth of fibroblasts and the formation of new blood vessels; 400MHz liquid nuclear magnetic resonance spectroscopy (NMR) and Fisher Scientific Nicolet iS20 Fourier transform infrared spectroscopy (FTIR) confirmed that the composition contains polylactic acid-glycolic acid copolymer (PLGA) and polydioxanone (PPDO), such as Figure 3 (b) shows a wave number of 2957.45 cm -1 The peak at 1419.02 cm is attributed to the stretching vibration of the methyl group (CH3) and methylene group (CH2) in PLGA and the stretching vibration of the methylene group (CH2) in PPDO; the wave number is 1419.02 cm -1 The peak at 1734.01 cm is attributed to the bending vibration of the methyl group (CH3) in PLGA, the bending vibration of the primary and tertiary alcohols in PLGA, and the bending vibration of the methylene group (CH2) in PPDO; the wave number is 1734.01 cm -1 The peak at 1129.73 cm is attributed to the stretching vibration of the ester bond (C=O) in PLGA and the stretching vibration of the carbonyl group (C=O) in PPDO. -1 and 1202.40 cm -1 The peak at 1089.67 cm is attributed to the stretching vibration of the ester bond (COC) in PLGA. -1 The peak at 1300 cm is attributed to the stretching vibration of the ether (COC) in PPDO. In summary, the infrared spectrum has the characteristic peaks of both PGLA and PPDO, especially in the fingerprint region (1300 cm -1 Up to 400cm -1 ), which is sufficient to prove that the composition contains both PLGA and PPDO. A phosphate buffer solution (PBS, PH=7.44) at 37 °C was selected as the in vitro degradation environment of the PLGA and PPDO electrospun functional membranes in the biodegradable tissue repair functional dressing 3. The obtained biodegradable tissue repair functional dressing 3 was immersed in a phosphate buffer solution at 37 °C, and the degradation time of the electrospun functional membrane was about 44 days.

[0055] According to the test methods in YY T 0471.1-2004, YYT 0471.2-2004 and YYT 0471.3-2004, it was found that the performance of the polyurethane foam material covered with the electrospun functional membrane of different polymer components in this embodiment was almost unchanged compared with that in Example 1: the liquid absorbency was not less than 9 times the initial mass (the total mass of the electrospun functional membrane and the polyurethane foam material with an area of ​​10 cm×10 cm); the liquid absorption was not less than 10.0 g·24 h -1 ; Water vapor transmission rate not less than 800 g·m -2 24h -1 ; The water barrier property reaches the standard of being able to withstand 500 mm hydrostatic pressure for 300 s without water seepage. However, the bonding strength between the electrospun functional membrane and the polyurethane foam material has increased: the average force required for every 1 cm width measured by the WDW-0.5 electronic universal testing machine is not less than 1.5 N, so that the two are sufficient to resist the friction generated during packaging and transportation, avoiding the separation and shedding of the electrospun functional membrane and the polyurethane foam material, and meeting the requirement of peeling off the polyurethane foam material that has absorbed tissue exudate during wound healing.

[0056] Example 4

[0057] The process and conditions are the same as in Example 3, except that: This embodiment provides a polyurethane foam material with a PU film (thickness of 0.035 mm) on one side, which replaces the polyurethane foam material in the above embodiment 3 to obtain a biodegradable tissue repair functional dressing 4, which can be compared with embodiment 3. The specific experimental contents are as follows: Under the environmental conditions of temperature of 25 ℃ and humidity of 50%, 20 mL of biodegradable spinning solution with a total content of PLGA and PPDO of 20 wt% was taken into a 20 mL syringe with a metal needle (model 20 G), and the syringe was connected to the injection pump.

[0058] The metal needle in step (1) was connected to the positive electrode, the receiving roller was connected to the negative electrode, and a polyurethane foam material with a PU film having an area of ​​30 cm×20 cm was adhered to the outer surface of the receiving roller.

[0059] After fixing the distance between the two electrodes at 15 cm, the scanning length of the TL-BM-300 high-voltage electrospinning machine was adjusted to 25 cm, the cleaning length was 10 cm, the scanning speed was 100 mm / s, the cleaning speed was 100 mm / s, the cleaning cycle was 10 times, the acceleration time was 60 s, the spinning time was 4 h, the cleaning time was 4 h, the micro pump flow rate was 5 mL / h, and the receiving roller speed was 300 rpm. Then, a high voltage of 22 KV was applied. After the spinning was completed, the electrospun fiber membrane and the polyurethane foam material with PU membrane were retained at the same time, and the electrospun fiber membrane and the polyurethane foam material with PU membrane were not separated, and finally a biodegradable tissue repair functional dressing 4 was obtained.

[0060] Since the components, concentrations and ratios of the electrospinning functional membrane layers of the biodegradable tissue repair functional dressing 3 and the biodegradable tissue repair functional dressing 4 are the same, and the spinning parameters are also the same, the test is not repeated here.

[0061] According to the test methods in YY T 0471.1-2004, YYT 0471.2-2004 and YYT 0471.3-2004, the results show that the polyurethane foam material with PU film (absorption layer with breathable film) has similar performance parameters to those of Example 2: the liquid absorbency is not less than 9 times the initial mass (the total mass of the electrospinning functional film and the polyurethane foam material with an area of ​​10 cm×10 cm); the liquid absorption is not less than 10.0 g·24 h -1 ; Water vapor transmission rate not less than 400 g·m -2 24h -1 ; The water barrier property reaches the standard of being able to withstand 500 mm hydrostatic pressure for 300 s without water seepage. Similarly, the bonding strength between the electrospun functional membrane and the polyurethane foam material is increased, which is consistent with Example 3: the average force required for every 1 cm width is not less than 1.5 N measured by the WDW-0.5 electronic universal testing machine, so that the two are sufficient to resist the friction generated during packaging and transportation, avoiding the separation and shedding of the electrospun functional membrane and the polyurethane foam material, and satisfying the requirement of peeling off the polyurethane foam material that has absorbed tissue exudate during wound healing.

[0062] Example 5

[0063] This example provides a method for preparing a high-content bicomponent biodegradable spinning solution, comprising the following steps: 20 g of poly(lactic acid-co-glycolic acid) (PLGA) and 30 g of hexafluoroisopropanol (HFIP) were added to a reagent bottle equipped with a magnetic stirring bar and stirred at a stirring rate of 500 rpm for 24 h in an oil bath at 50 °C until completely dissolved to obtain a biodegradable spinning solution containing 40 wt% PLGA.

[0064] 20 g of polydioxanone (PPDO) and 30 g of hexafluoroisopropanol (HFIP) were added to a reagent bottle equipped with a magnetic stirring bar, and stirred at a stirring rate of 500 rpm in an oil bath at 50 °C for 24 h until completely dissolved to obtain a biodegradable spinning solution containing 40 wt% PPDO.

[0065] 10 mL of biodegradable spinning solution containing 40 wt% PLGA and 10 mL of biodegradable spinning solution containing 40 wt% PPDO were weighed respectively and added into a reagent bottle equipped with a magnetic stirring bar. The mixture was stirred continuously at a stirring rate of 500 rpm for 4 h in an oil bath at 50 °C until the mixture was uniformly mixed, thereby obtaining a biodegradable spinning solution with a total content of PLGA and PPDO of 40 wt%.

[0066] This example provides a biodegradable tissue repair functional dressing 5 obtained by spinning technology using the above-mentioned biodegradable spinning solution with a total content of PLGA and PPDO of 40 wt%, which can be compared with Example 4 to clarify the effect of a high content of solute in the spinning solution on the structure of the electrospinning functional membrane layer. The specific experimental content is as follows: Under the environmental conditions of temperature of 25 ℃ and humidity of 50%, 20 mL of biodegradable spinning solution with a total content of PLGA and PPDO of 40 wt% was taken into a 20 mL syringe with a metal needle (model 20 G), and the syringe was connected to the injection pump.

[0067] The metal needle in step (1) was connected to the positive electrode, the receiving roller was connected to the negative electrode, and a polyurethane foam material with a PU film having an area of ​​30 cm×20 cm was adhered to the outer surface of the receiving roller.

[0068] After fixing the distance between the two electrodes at 15 cm, the scanning length of the TL-BM-300 high-voltage electrospinning machine was adjusted to 25 cm for scanning, 10 cm for cleaning, 100 mm / s for scanning, 100 mm / s for cleaning, 10 cleaning cycles, 60 s for acceleration, 4 h for spinning, 4 h for cleaning, 5 mL / h for flow rate of the micro pump, and 300 rpm for receiving roller speed. Then, a high voltage of 22 KV was applied. After spinning, the electrospun fiber membrane and the polyurethane foam material with PU membrane were retained at the same time, and the electrospun fiber membrane and the polyurethane foam material with PU membrane were not separated, and finally a biodegradable tissue repair functional dressing 5 was obtained.

[0069] The electrospinning functional film layer of the biodegradable tissue repair functional dressing 5 was characterized and analyzed, and the results were as follows: Regulus8100 scanning electron microscope (SEM) showed that its fiber diameter was about 800 nm~2000 nm, the film thickness was about 185 μm, and the fiber diameter value was mostly coincident with the value specified in the technical requirements (30 nm~2000 nm), but the small-sized fiber diameter was missing; the fiber pore size was measured by Autopore V 9620 high-performance fully automatic mercury intrusion instrument in the range of 0.89 μm~316 μm, and the porosity was greater than 50%, which can meet the needs of fibroblast ingrowth, skin regeneration, cell infiltration and tissue growth. Finally, the components of the spinning solution did not change compared with Example 4, and the composition verification of 400MHz liquid nuclear magnetic resonance spectroscopy (NMR) and Fisher Scientific Nicolet iS20 Fourier transform infrared spectroscopy (FTIR) was not repeated here. A phosphate buffer solution (PBS, PH=7.44) at 37 ℃ was selected as the in vitro degradation environment of the PLGA and PPDO electrospun functional membranes in the biodegradable tissue repair functional dressing 5. The obtained biodegradable tissue repair functional dressing 5 was immersed in the phosphate buffer solution at 37 ℃, and the degradation time of the electrospun functional membrane was about 82 days.

[0070] Since the polyurethane foam material with PU film of biodegradable tissue repair functional dressing 5 is the same as that of biodegradable tissue repair functional dressing 4, other characterization tests are not repeated here. Only the bonding strength between the electrospinning functional film and the polyurethane foam material is slightly increased: the average force required for every 1 cm width is not less than 2.7 N measured by WDW-0.5 electronic universal testing machine, which still meets the requirements of packaging and transportation and separation and shedding on demand.

[0071] Example 6

[0072] The biodegradable tissue repair functional dressing 4 in Example 4 was used as the test group to explore its effects on cell morphology and in vitro cytotoxicity.

[0073] Experimental group: Under sterile operation, the flat part of the test sample was cut into discs with a diameter of 1.0 cm, of which the thickness of the electrospinning functional layer was 100 μm, with a total of 3 discs.

[0074] Negative control group: under aseptic operation, the flat part of the high-density polyethylene film was cut into discs with a diameter of 1.0 cm. The thickness of the film was 100 μm, and there were 3 discs in total.

[0075] Positive control group: Cut the flat part of the latex gloves into 1.0 cm diameter discs, 3 discs in total.

[0076] Blank control sample: MEM medium containing 10% fetal bovine serum.

[0077] Experimental steps: First, mouse fibroblasts (L-929 cells) were cultured in MEM medium containing 10% fetal bovine serum and then placed in a 37°C, 5% CO2 incubator for culture. Then, a cell suspension (4×10 4 2 mL of 5% paraformaldehyde (p / mL) was added to a 35 mm diameter dish to culture a monolayer of cells. The dish was gently rotated horizontally to evenly disperse the cells on the surface of the dish. The dish was cultured in a cell culture incubator for 24 hours until the monolayer of cells was nearly confluent. The culture medium was removed and replaced with 0.8 mL of fresh culture medium.

[0078] Place one test sample, positive control and negative control separately in each culture dish, and set up three parallels for each sample to ensure that the sample covers about one-tenth of the cell layer surface.

[0079] All cultures were cultured in a cell culture incubator at 37°C with 5% CO2 for at least 24 hours, and the surroundings of each test article, negative control, and positive control were observed under a microscope.

[0080] Observation of cell number and morphology under the CKX53 inverted biological microscope showed that the adherent cells in the negative control group were relatively sparse. Figure 4 (a) It can be observed that the number and density of cell proliferation are much lower than those in the test group; under the conditions of this test, the toxicity of the test sample to L-929 cells is grade 1 (see Table 1 for details of the reaction rating), indicating that the test sample is not cytotoxic to L-929 cells, and Figure 4The number and density of cell proliferation in (b) were at least twice that of the negative control group. The positive control group was severely cytotoxic, and almost no adherent cells were observed. It can be concluded that the biodegradable tissue repair functional dressing is conducive to cell proliferation, migration and differentiation, sufficient to support cell ingrowth, the formation of new blood vessels and the rapid growth of tissues, and does not show in vitro cytotoxicity.

[0081] Table 1 Cytotoxicity ratings Grading Degree of reaction Reaction area observation 0 none No reaction area was observed around or under the sample. 1 slight There are some deformed or degenerated cells under the sample 2 Mild The reaction area is limited to the bottom of the sample 3 Moderate The reaction area exceeds the sample size to 1.0 cm 4 Severe The reaction area exceeds the sample size by more than 1.0 cm Comparative Example 1 This example provides a method for preparing a two-component biodegradable spinning solution with excessively high solute content, comprising the following steps: 25 g of poly(lactic acid-co-glycolic acid) (PLGA) and 25 g of hexafluoroisopropanol (HFIP) were added to a reagent bottle equipped with a magnetic stirring bar, and stirred at a stirring rate of 500 rpm for 48 h in an oil bath at 50 °C until completely dissolved to obtain a biodegradable spinning solution containing 50 wt% PLGA.

[0082] 25 g of polydioxanone (PPDO) and 25 g of hexafluoroisopropanol (HFIP) were added to a reagent bottle equipped with a magnetic stirring bar, and stirred at a stirring rate of 500 rpm in an oil bath at 50 °C for 48 h until completely dissolved to obtain a biodegradable spinning solution containing 50 wt% PPDO.

[0083] 10 mL of biodegradable spinning solution containing 50 wt% PLGA and 10 mL of biodegradable spinning solution containing 50 wt% PPDO were weighed respectively and added into a reagent bottle equipped with a magnetic stirring bar. The mixture was stirred continuously at a stirring rate of 500 rpm for 12 h in an oil bath at 50 °C until the mixture was uniformly mixed, thereby obtaining a biodegradable spinning solution with a total content of PLGA and PPDO of 50 wt%.

[0084] This example provides a biodegradable tissue repair functional dressing 6 obtained by spinning technology using the above-mentioned biodegradable spinning solution with a total content of PLGA and PPDO of 50 wt%, which can be compared with Example 5 to clarify the influence of the solute content in the spinning solution on the structure of the electrospinning functional membrane layer. The specific experimental contents are as follows: Under the environmental conditions of temperature of 25 ℃ and humidity of 50%, 20 mL of biodegradable spinning solution with a total content of PLGA and PPDO of 50 wt% was loaded into a 20 mL syringe with a metal needle (model 20 G), and the syringe was connected to the injection pump.

[0085] The metal needle in step (1) was connected to the positive electrode, the receiving roller was connected to the negative electrode, and a polyurethane foam material with a PU film having an area of ​​30 cm×20 cm was adhered to the outer surface of the receiving roller.

[0086] After fixing the distance between the two electrodes at 15 cm, the scanning length of the TL-BM-300 high-voltage electrospinning machine was adjusted to 25 cm for scanning, 10 cm for cleaning, 100 mm / s for scanning, 100 mm / s for cleaning, 10 cleaning cycles, 60 s for acceleration, 4 h for spinning, 4 h for cleaning, 5 mL / h for flow rate of the micro pump, and 300 rpm for receiving roller speed. Then, a high voltage of 22 KV was applied. After the spinning was completed, the electrospun fiber membrane and the polyurethane foam material with PU membrane were retained at the same time, and the electrospun fiber membrane and the polyurethane foam material with PU membrane were not separated, and finally a biodegradable tissue repair functional dressing 6 was obtained.

[0087] The electrospun functional membrane layer of biodegradable tissue repair functional dressing 6 was characterized and analyzed, and the results were as follows: Regulus8100 scanning electron microscope (SEM) showed that its fiber diameter was about 1100 nm~3400 nm and the film thickness was about 260 μm. The fiber diameter values ​​were generally too large, and only a very small part coincided with the values ​​specified in the technical requirements (30 nm~2000 nm), which did not meet the needs of cell proliferation, migration and differentiation; and the excessively thick electrospun functional membrane layer transition prolonged the degradation cycle; Autopore V 9620 high-performance fully automatic mercury intrusion instrument measured the fiber pore size in the range of 0.6 μm~89 μm, and the porosity was greater than 37%. Due to the increase in fiber diameter and film thickness, the pore size and porosity were further reduced, resulting in the obstruction of skin regeneration, new blood vessel formation, cell infiltration and tissue growth. Finally, the composition of the spinning solution did not change compared with Example 5, and the composition verification of 400MHz liquid nuclear magnetic resonance spectroscopy (NMR) and Fisher Scientific Nicolet iS20 Fourier transform infrared spectroscopy (FTIR) was not repeated here. A 37°C phosphate buffer solution (PBS, PH=7.44) was selected as the in vitro degradation environment of the PLGA and PPDO electrospinning functional membranes in the biodegradable tissue repair functional dressing 6, and the obtained biodegradable tissue repair functional dressing 6 was immersed in a 37°C phosphate buffer solution, and the degradation time of the electrospinning functional membrane was about 115 days.

[0088] Since the polyurethane foam material with PU film of biodegradable tissue repair functional dressing 6 is the same as that of biodegradable tissue repair functional dressing 5, other characterization tests are not repeated here. Only the bonding strength between the electrospinning functional film and the polyurethane foam material is further increased: the average force required for each 1 cm width is measured by a WDW-0.5 electronic universal testing machine and is not less than 3.3 N, which still meets the requirements of packaging and transportation and separation and shedding on demand.

[0089] Comparative Example 2 The process and conditions are the same as those of Example 4, except that high pressure is applied to obtain a biodegradable tissue repair functional dressing 7, in order to explore the effect of high pressure on the structure and spinnability of the electrospinning functional membrane layer. The specific experimental contents are as follows: Under the environmental conditions of temperature of 25 ℃ and humidity of 50%, 20 mL of biodegradable spinning solution with a total content of PLGA and PPDO of 20wt% was taken into a 20 mL syringe with a metal needle (model 20G), and the syringe was connected to the injection pump.

[0090] The metal needle in step (1) was connected to the positive electrode, the receiving roller was connected to the negative electrode, and a polyurethane foam material with a PU film having an area of ​​30 cm×20 cm was adhered to the outer surface of the receiving roller.

[0091] After fixing the distance between the two electrodes at 15 cm, the scanning length of the TL-BM-300 high-voltage electrospinning machine was adjusted to 25 cm, the cleaning length was 10 cm, the scanning speed was 100 mm / s, the cleaning speed was 100 mm / s, the cleaning cycle was 10 times, the acceleration time was 60 s, the spinning time was 4 h, the cleaning time was 4 h, the micro pump flow rate was 5 mL / h, and the receiving roller speed was 300 rpm. Then, a high voltage of 38 KV was applied. After the spinning was completed, the electrospun fiber membrane and the polyurethane foam material with PU membrane were retained at the same time, and the electrospun fiber membrane and the polyurethane foam material with PU membrane were not separated, and finally a biodegradable tissue repair functional dressing 7 was obtained.

[0092] The electrospinning functional membrane layer of the biodegradable tissue repair functional dressing 7 was characterized and analyzed, and the results were as follows: Regulus8100 scanning electron microscope (SEM) showed that its fiber diameter was about 10 nm~1020 nm and the film thickness was about 80 μm. Compared with Example 4, the fiber diameter was slightly reduced and could not completely cover the value specified in the technical requirements (30 nm~2000 nm), which was not conducive to the needs of cell proliferation, migration and differentiation; the fiber pore size was measured by Autopore V 9620 high-performance fully automatic mercury intrusion instrument in the range of 200 μm~700 μm, the pore size range was too large, and it failed to meet the needs of small-pore fibroblasts to grow inward, and the porosity was >92%, which still met the cell infiltration and tissue growth. Finally, the components of the spinning solution did not change compared with Example 4, and the composition verification of 400MHz liquid nuclear magnetic resonance spectroscopy (NMR) and FisherScientific Nicolet iS20 Fourier transform infrared spectroscopy (FTIR) was not repeated here. A phosphate buffer solution (PBS, PH=7.44) at 37 ℃ was selected as the in vitro degradation environment of the PLGA and PPDO electrospun functional membranes in the biodegradable tissue repair functional dressing 7. The obtained biodegradable tissue repair functional dressing 7 was immersed in the phosphate buffer solution at 37 ℃, and the degradation time of the electrospun functional membrane was about 36 days.

[0093] Since the polyurethane foam material with PU film of biodegradable tissue repair functional dressing 7 is the same as that of biodegradable tissue repair functional dressing 4, other characterization tests are not repeated here. Only the bonding strength between the electrospinning functional film and the polyurethane foam material is increased: the average force required for each 1 cm width is not less than 1.9 N, which still meets the requirements of packaging and transportation and separation and shedding on demand.

[0094] In addition to the characterization of the above technical parameters, there are also abnormalities in the spinnability of the electrospinning process, that is, the applied high voltage is too large, which causes the electric field strength to continuously increase, resulting in an increase in the jet volume of the spinning solution each time and an increase in the jet speed, which is not conducive to the stretching and splitting of the jet, thereby increasing the fiber diameter and worsening the uniformity, resulting in beaded or beaded nanofibers.

[0095] Comparative Example 3 The process and conditions are the same as those in Example 4, except that the flow rate of the micro pump is increased dramatically to obtain a biodegradable tissue repair functional dressing 8, in order to explore the effect of excessively high flow rate on the structure, spinnability and film quality of the electrospun functional membrane layer. The specific experimental contents are as follows: This example provides a method for preparing a two-component biodegradable spinning solution 4, comprising the following steps: Under the environmental conditions of temperature of 25 ℃ and humidity of 50%, 20 mL of biodegradable spinning solution with a total content of PLGA and PPDO of 20 wt% was taken into a 20 mL syringe with a metal needle (model 20 G), and the syringe was connected to the injection pump.

[0096] The metal needle in step (1) was connected to the positive electrode, the receiving roller was connected to the negative electrode, and a polyurethane foam material with a PU film having an area of ​​30 cm×20 cm was adhered to the outer surface of the receiving roller.

[0097] After fixing the distance between the two electrodes at 15 cm, the scanning length of the TL-BM-300 high-voltage electrospinning machine was adjusted to 25 cm for scanning, 10 cm for cleaning, 100 mm / s for scanning, 100 mm / s for cleaning, 10 cleaning cycles, 60 s for acceleration, 0.5 h for spinning, 0.5 h for cleaning, 30 mL / h for flow rate of the micro pump, and 900 rpm for receiving drum speed. Then, a high voltage of 22 KV was applied. After spinning, the electrospun fiber membrane and the polyurethane foam material with PU membrane were retained at the same time, and the electrospun fiber membrane and the polyurethane foam material with PU membrane were not separated, and finally a biodegradable tissue repair functional dressing 8 was obtained.

[0098] The electrospinning functional membrane layer of the biodegradable tissue repair functional dressing 8 was characterized and analyzed, and the results were as follows: Regulus8100 scanning electron microscope (SEM) showed that its fiber diameter was about 1010 nm~3600 nm and the film thickness was about 290 μm. The value of the fiber diameter was similar to that of Comparative Example 1, which did not meet the requirements for cell proliferation, migration and differentiation; similarly, the excessively thick electrospinning functional membrane layer transition extended the degradation cycle; the fiber pore size was measured by Autopore V 9620 high-performance fully automatic mercury intrusion instrument in the range of 0.3 μm~52 μm, and the porosity was greater than 30%, which was not conducive to skin regeneration, new blood vessel formation, cell infiltration and tissue growth. Finally, the components of the spinning solution did not change compared with Example 4, and the composition verification of 400MHz liquid nuclear magnetic resonance spectroscopy (NMR) and Fisher Scientific Nicolet iS20 Fourier transform infrared spectroscopy (FTIR) was not repeated here. A phosphate buffer solution (PBS, PH=7.44) at 37°C was selected as the in vitro degradation environment of the PLGA and PPDO electrospun functional membranes in the biodegradable tissue repair functional dressing 8. The obtained biodegradable tissue repair functional dressing 8 was immersed in the phosphate buffer solution at 37°C, and the degradation time of the electrospun functional membrane was about 128 days.

[0099] Since the polyurethane foam material with PU film of biodegradable tissue repair functional dressing 8 is the same as that of biodegradable tissue repair functional dressing 4, other characterization tests are not repeated here. Only the bonding strength between the electrospinning functional film and the polyurethane foam material is slightly reduced: the average force required for each 1 cm width is not less than 1.2 N, but it still meets the requirements of packaging and transportation and separation and shedding on demand.

[0100] In addition to the characterization of the above technical parameters, there are also abnormalities in the spinnability of the electrospinning process, that is, with the increase of spinning speed, the diameter of the prepared nanofibers will gradually increase. Since the nanofiber jet is not completely dried during the flight between the needle tip and the metal collector, it may even lead to the formation of beaded fibers, which is manifested macroscopically as a large number of impurity particles on the surface of the film.

[0101] In summary, the biodegradable tissue repair functional dressing can temporarily serve as a tissue scaffold for the dermis and epidermis during the wound healing process, shorten the cell proliferation, migration and differentiation cycle, promote the formation of new blood vessels and tissue growth, and fully restore the two layers of tissue. The degradable components of the functional dressing can also avoid secondary damage caused by frequent dressing changes and wound debridement. In addition, the absorption layer of the functional dressing also plays a role in absorbing tissue exudate, maintaining a moist healing environment for the wound, and protecting the wound from contamination until the wound heals. Therefore, the biodegradable tissue repair functional dressing has opened up a biomaterial that can be used for a variety of clinical indications in the process of wound care.

Claims

1. A biodegradable tissue repair functional dressing, comprising an electrospinning functional membrane layer and an absorption layer, characterized in that: The electrospinning functional membrane layer is prepared from a biodegradable high molecular polymer by electrospinning technology, and the biodegradable high molecular polymer is selected from one or more of polydioxanone, polyε-caprolactone, polydioxanone-ε-caprolactone copolymer, polyglycolic acid, polyvinyl lactone-ε-caprolactone copolymer, polylactic acid-glycolic acid copolymer, polydextrorotatory-lactic acid, polylactic acid-ε-caprolactone copolymer, polylactic acid, polytrimethylene carbonate, polydodecylglycerol, and poly(ω-pentadecanolactone); one side of the absorption layer may or may not have a breathable membrane.

2. The biodegradable tissue repair functional dressing according to claim 1, characterized in that: The fiber diameter of the electrospun functional membrane layer is 1 nm to 2000 nm.

3. The biodegradable tissue repair functional dressing according to claim 1, characterized in that: The porosity of the electrospun functional membrane layer is greater than 40%, and the average pore size is 1 μm to 1000 μm.

4. The biodegradable tissue repair functional dressing according to claim 1, characterized in that: The thickness of the electrospun functional membrane layer is 0.1 μm to 1000 μm.

5. The biodegradable tissue repair functional dressing according to claim 1, characterized in that: The material used for the absorption layer is any one or more of fiber, gel, hydrocolloid, and foaming material. When one side of the absorption layer is provided with a breathable film, the breathable film is selected from any one of polyethylene film, polypropylene film, and polyurethane film. The thickness of the absorption layer is 0.1 mm to 5 mm, wherein the thickness of the breathable film is 0.012 mm to 0.035 mm.

6. The biodegradable tissue repair functional dressing according to claim 1, characterized in that: The bonding strength between the electrospun functional membrane layer and the absorption layer is 1~5 N / cm.

7. A method for preparing the biodegradable tissue repair functional dressing according to any one of claims 1 to 6, characterized in that: The biodegradable tissue repair functional dressing is prepared by classical spinning technology, and the preparation process is as follows: (1) Preparing a spinning solution: adding a biodegradable high molecular polymer to a volatile organic reagent, stirring at a certain temperature until the polymer is completely dissolved, and preparing the desired spinning solution; (2) Under the environmental conditions of temperature of 18-40°C and humidity of 30%-80%, load the spinning solution into a syringe with a metal needle and ensure that the syringe and the injection pump are connected to each other; (3) The metal needle in step (2) is connected to the positive electrode, the receiving end is connected to the negative electrode, and a receiving substrate with an area of ​​30 cm × 20 cm is fixed on the outer surface of the receiving end; (4) After fixing the distance between the two electrodes, the scanning length, cleaning length, scanning speed, cleaning speed, cleaning cycle, acceleration time, spinning time, cleaning time, micro pump flow rate, and receiving speed of the electrospinning machine are adjusted in sequence, and then high voltage is applied; after the spinning is completed, the electrospinning fiber membrane and the receiving substrate are retained at the same time to prepare a biodegradable tissue repair functional dressing.

8. The method for preparing the biodegradable tissue repair functional dressing according to claim 7, characterized in that: The biodegradable high molecular polymer in step (1) is selected from one or more of polydioxanone, polyε-caprolactone, polydioxanone-ε-caprolactone copolymer, polyglycolic acid, polyvinyl lactone-ε-caprolactone copolymer, polylactic acid-glycolic acid copolymer, polydextrorotatory-lactic acid, polylactic acid-ε-caprolactone copolymer, polylactic acid, polytrimethylene carbonate, polydodecylglycerol, and poly(ω-pentadecanolactone).

9. The method for preparing the biodegradable tissue repair functional dressing according to claim 7, characterized in that: In step (1), the volatile organic reagent is one or more of chloroform, methanol, toluene, dichloromethane, hexafluoroisopropanol, tetrahydrofuran, acetone or N,N'-dimethylformamide; In step (1), the mass percentage of the biodegradable high molecular polymer in the spinning solution is 1-40 wt%; The stirring temperature in step (1) is 30-80°C, the stirring speed is 50-1500 rpm, and the stirring time is 2-48 h.

10. The method for preparing the biodegradable tissue repair functional dressing according to claim 7, characterized in that: The model of the metal needle in step (2) is 10 G~30 G; The volume of the syringe in step (2) is 1 mL to 50 mL; In step (3), the receiving end may be a metal plate, a roller or a metal wire; In step (3), the receiving substrate is an absorbent layer with or without a breathable film, and the absorbent layer material is any one or more of fiber, gel, hydrocolloid, and foaming material, wherein the breathable film is a polyethylene film, a polypropylene film, or a polyurethane film; The distance between the two poles in step (4) is 5 to 30 cm; The scanning length in step (4) is 5 to 50 cm; The cleaning length in step (4) is 5 to 20 cm; The scanning speed in step (4) is 5-300 mm / s; The cleaning speed in step (4) is 5-300 mm / s; The cleaning cycle in step (4) is 1 to 30 times; The acceleration time in step (4) is 1 to 600 s; The spinning time in step (4) is 1 to 24 hours; The cleaning time in step (4) is 1 to 24 hours; The flow rate of the micro pump in step (4) is 0.1-20 mL / h; The receiving speed in step (4) is 1-5000 rpm; The high voltage applied in step (4) is 1~30 KV.

Citation Information

Patent Citations

  • Modified cellulose nanofiber membrane based on layer-by-layer self-assembly of lysozyme and silk protein based as well as preparation and application thereof

    CN103536958B

  • An absorbable oral repair membrane and its preparation method

    CN109513046B

  • Wound dressing as well as preparation method and application thereof

    CN113293626A

  • Scar-free regenerated medicinal dressing with tissue induction function and preparation method of scar-free regenerated medicinal dressing

    CN107638587A

  • Electrospinning dressing loading growth factor small molecule inhibitor, preparation method and applications thereof

    CN109381732A

Cited By

  • Array substrate, preparation method of array substrate and display panel

    CN119894093A